Reversal of the Underdog Through Technological Focus and Creative Mechanism: A SER-M Based Strategic Case Study of Alteogen (aSSIST Business Review, 2026)
This study analyzes how the Korean biotech venture Alteogen implemented a strategy of “the weak defeating the strong” by applying the SER-M  (Subject–Environment–Resources–Mechanism)  framework.  Despite  its  limited  capital  and  scale,  Alteogen  achieved  global recognition and strategic partnerships with major pharmaceutical companies through a technology-driven approach. Anchored in the founder’s philosophy and entrepreneurial vision (Subject), the company identified structural changes in the pharmaceutical industry and the rising demand for  intravenous-to-subcutaneous drug delivery (Environment). By developing and patenting  its proprietary human hyaluronidase platform, ALT-B4 (Resources), Alteogen executed a creative mechanism  (Mechanism)  through non-exclusive  licensing strategies and global alliances. This approach enabled the company to secure cumulative licensing contracts worth approximately 9 trillion KRW  with  partners  such  as  Merck,  AstraZeneca,  and  Daiichi  Sankyo,  thereby  validating  its  competitiveness  and  performance (Performance). The findings demonstrate that biotech ventures, even with resource constraints, can reshape industrial power structures by focusing on original platform technologies, strategic resource reconfiguration, and agile decision-making. Moreover, the case illustrates the explanatory power of the SER-M model in interpreting how smaller firms can gain leverage against established incumbents, offering strategic implications not only for the biotech sector but also for other innovation-driven industries.
Keywords: SER-M model; creative mechanism; Alteogen; biobetter; Korean strategy; underdog strategy